Intervention to address childhood undernutrition: A systematic review - Tan, Eric Chee How; Marilyn Maluda; Mohd. Yusof Ibrahim; Lim, Kai Joo; Aza Sherin Mohd Yusuff; Khamisah Awang Lukman (Penerbit UMS, 2022)
Introduction: Childhood undernutrition while being a preventable condition remains a major public health issue because it contributes to the mortality and morbidity of children globally. Intervention strategies to improve the nutritional status of children include therapeutic food, cash transfers, antibiotics and nutritional education. The objective is to review the effects of various nutritional interventions in addressing undernutrition in children. Methods: Comprehensive search of literature in electronic databases were conducted in PubMed, Science Direct, and Scopus containing the Medical Subject Headings (MeSH) and the title terms ‘Undernutrition’ OR ‘Malnutrition AND ‘Intervention’ OR ‘Management’ AND ‘Children’ OR ‘Childhood’ between January 2000 and August 2019. Of the 4358 studies that were identified, 17 studies matched the inclusion criteria and were reviewed. Results: Therapeutic food is an integral part of nutritional interventions in majority of the studies along with cash transfers and nutritional education. The most consistent outcome in most of the studies was improvement in the nutritional status which subsequently reduces the undernutrition in children. Conclusion: Therapeutic food, conditional cash transfer and nutritional education yielded the best outcome in alleviating undernutrition in developing countries.